Sifat Fisis Mortar Dengan Perkuatan Serat Kayu Kelapa Sawit dan Crystalline Admixture - Tarmizi Tarmizi; Cut Rahmawati; Amri Amin (Jurnal Teknik Sipil Unaya, 2023)
The aim of the study was to analyze the physical properties, mechanical properties and effective composition of the fibers in the bio-panel added with PSC and CAs fibers. This research was carried out by making test objects in the laboratory with variations in the addition of fiber 0%, 1%, 2%, 3% with 3 test objects for each variation, the raw materials used were cement, CAs, water and PSC fiber. The tests carried out included testing the physical properties of workability, yield stress, bulk density, and water absorption. The mechanical strength tested was flexural strength and fracture toughness. The results of the workability examination with the addition of 3% fiber can reduce the flow by 22.03%. The results of the yield stress with the addition of 3% KKS fiber can increase the yield stress by 52.91%. From the bulk density results, it showed that the addition of 3% of KKS fiber actually lowered the density. The bulk density values obtained were in the range of 1.2-1.6 g/cm3. And the results of examining the water absorption capacity obtained the lowest water absorption capacity in the test object with the addition of 2% fiber by 4.50%. In the test object with a fiber percentage of 3%, the water absorption capacity reached 5.53%, this was due to the use of too much fiber causing the fibers to agglomerate. The evaluation of physical properties shows that KKS fiber is very potential and feasible as a reinforcement in bio-panel products.